Development and testing of a plastic bolus for gamma therapy; Innovative Technologies of Nuclear Medicine and Radiation Diagnostics and Therapy - Sorokina A. A. Aida Arsenovna; Bulavskaya A. A. Angelina Aleksandrovna; Bushmina E. A. Elizaveta Alekseevna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2022, 2022)
Title screen